2006
DOI: 10.1111/j.1095-8339.2006.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

A feeling for the micro-organism: structure on a small scale. Biofilms on plant roots

Abstract: Biofilms are structured communities of bacterial cells enclosed in a self-produced polymeric matrix and adherent to an inert or living surface; they have clinical, industrial and environmental impacts. Biofilms that are established by bacteria on plants are found on the surfaces of roots, leaves, seeds and internal vascular tissues where the microbes live in commensal, mutualistic or parasitic/pathogenic associations with their host. The study of the structure of plant-associated biofilms has been considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 57 publications
2
36
0
5
Order By: Relevance
“…Moreover, increasing the production of exopolysaccharide against higher salt stress leads to support biofilm formation (Ishii et al, 2004;Fujishige et al, 2006). These results are in agreement with those obtained by Arora et al (2010), Qurashi and Sabri (2012), Deng et al (2015) and Kasim et al (2016).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, increasing the production of exopolysaccharide against higher salt stress leads to support biofilm formation (Ishii et al, 2004;Fujishige et al, 2006). These results are in agreement with those obtained by Arora et al (2010), Qurashi and Sabri (2012), Deng et al (2015) and Kasim et al (2016).…”
Section: Discussionsupporting
confidence: 82%
“…Transmission electron microscopy has shown the presence of fibrillar material around rhizobia attached to the root surface (Fujishige et al, 2006). These observations further support the proposal that root colonizing bacteria are capable of forming biofilms, it is reasonable to suppose that the molecular mechanisms operating in bacterial attachment to roots also might be relevant for biofilm development.…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2037-2047supporting
confidence: 71%
“…On the other hand, the results of this study indicated that rhizobial strains Rt24.2(pBA1) and Rt24.2(pBR1), which overproduced EPS had a significantly increased ability to adhere to different surfaces, including soil particles and the host roots, which ensured better survival and adaptation to changing environmental conditions. Similarly in S. meliloti, EPS is required for biofilm development, since an exoY mutant non-producing this polymer forms an immature biofilm (Fujishige et al 2006a;2006b). In this bacterium, a symbiotically active low-molecular-weight fraction of galactoglucan proved to be crucial for biofilm formation and colonisation of host plant roots (Rinaudi and González 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For this experiment, the method described by Fujishige et al (2006a) was applied with a slight modification. Suspensions of rhizobial strains were made in Fåhraeus liquid medium with OD 600 =0.1.…”
Section: Attachment Assay Of Rhizobia To Clover Rootsmentioning
confidence: 99%
See 1 more Smart Citation